The earthquakes on 12 April 1998 and 12 July 2004 in Krn Mountains (NW Slovenia) - time distribution of aftershocks and magnitude-frequency relation - Gosar, Andrej (Geologija, 2008)
Earthquakes on 12 April 1998 (ML=5.6) and 12. July 2004 (ML =4.9) in Krn Mountains were followed by extensive aftershock sequences with several thousand of shocks which lasted for more than one year. In 400 days the first earthquake was followed by 104 and the second one by 89 aftershocks with ML≥2,0. Both strongest aftershocks had magnitudes smaller for 1.4 and 1.3 with respect to the mainshocks, which is slightly more than published values (1.2). Analysis of time distribution of aftershocks with maximum likelihood estimate has shown that the parameters of modified Omori’s law, which describes the hyperbolic decay of aftershock activity with time, are very similar. This corresponds to the fact that both earthquakes occurred in the same hypocentral area. The value of p parameter is around 1.02. Aftershocks in 1998 clearly show secondary aftershock sequence which started with strongest aftershock on 6 May 1998 (ML=4.2), but there was no secondary sequence in 2004. Analysis of magnitude- frequency (Gutenberg-Richter’s) relation with least squares and maximum likelihood estimate has given the value of b parameter for 1998 aftershock sequence between 0.77 and 0.83 and for 2004 sequence between 0.97 and 0.98. This means that the first earthquake was followed by more stronger aftershocks. Obtained parameters of modified Omori’s law and Gutenberg-Richter’s relation are in good agreement with values published for similar aftershock sequences.